Аксіосфера права як філософсько-правова категорія - Горобець, К. В.; Горобец, К. В.; Gorobec, K. (Одеса : Юрид. л-ра, 2012)
Article deals with methodological and ontological analysis of the system of values in law, so called «axiosphere». It is proved that axiosphere of law is the subject of juridical and philosophical discurses. The content of axiosphere of law and its connections with legal reality have been shown.
Горобець К. В. Аксіосфера права як філософсько-правова категорія / К. В. Горобець // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 178-186.
Keywords: філософія права; правова аксіологія; цінності правової сфери; аксіосфера права; философия права; правовая аксиология; ценности правовой сферы; аксиосфера права; jurisprudence; legal axiology; values of legal sphere; axiosphere of law